If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.17a + 7 = 2 Reorder the terms: 7 + 0.17a = 2 Solving 7 + 0.17a = 2 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 0.17a = 2 + -7 Combine like terms: 7 + -7 = 0 0 + 0.17a = 2 + -7 0.17a = 2 + -7 Combine like terms: 2 + -7 = -5 0.17a = -5 Divide each side by '0.17'. a = -29.41176471 Simplifying a = -29.41176471
| 44=4(2y+3) | | v^2=-2v+24 | | .5a+5=-4 | | z^3-7z^2+10z=0 | | .04x+.03(5000-x)=180 | | z=m^2-m(1-SQRT(-1))-3(2+SQRT(-1)) | | 2j=64 | | 2j=6473554256376468578575364262 | | factorisex^2-1-42=0 | | 5(d+15)=90 | | 0=x-11-2x | | 12x+10=12x-8 | | x^2-1-42=0 | | -4x-13x=136 | | 3z=-174 | | 8z+4z=48 | | 8s-5=-5+5s | | -7x-23=-163 | | -(-27)d=16.2 | | 4x-12=64+2x | | 184=4(9)(4)+2(4)H | | ln(6x+1)=2 | | (8+x)*3-1=62 | | 3(x-4)+7=2x+1 | | 3p-17=-7+p | | 36-25/5+3*3= | | 36-25/5+3*3=40 | | 8+x*3-1=62 | | -9s=6 | | s(t)=-16t^2+44t+4 | | 4x-2(x-4)=-5+4x+7 | | z=m^2-m(1-i)-3(2+i) |